Сенсор на основі фотонно-кристалічного інтерферометра Маха-Цендера - Россохатська, А. С. (ХНУРЕ, 2020)
Model of photonic crystal sensor is considered in this work. Sensor scheme is based on the Mach-Zehnder interferometer. Dispersion characteristics of the bulk photonic crystal are obtained using free package MIT Photonic Bands. Package MEEP is used for numerical calculations of spectral characteristics of the structure. Sensitivity of the sensor is determined by resonance frequency shift after filling of sensor by investigated medium.
Keywords: сенсор; інтерферометр Маха-Цендера; фотонний кристал